EKSPERIMENTASI MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) BERBANTUAN MEDIA INTERAKTIF PADA MATERI PELUANG DITINJAU DARI GAYA BELAJAR SISWA - Elywati, Elywati; Budiyono, Budiyono; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2014)
Abstract. The goals of the research were to discover: (1) which learning model has better academic achievements, the Think Pair Share (TPS) learning model aided by interactive media, TPS, or the direct learning model; (2) which has better academic achievements, students having a visual, auditory, or kinesthetic learning style; (3) which has better academic achievements, students having a visual, auditory, or kinesthetic learning style for each of the different learning models and (4) which has better academic achievements, the TPS learning model aided by interactive media, TPS, or the direct learning model for each of the different learning styles. The type of research was quasi-experimental research. The population of the research was all class XI students in state high schools in the Sukoharjo district during the academic year 2013/2014. The number of sample members in the research was 306 students, with 205 students in the experimental class and 101 students in the control class. Samples were collected using a method of stratified cluster random sampling. The method used for analyzing data was a unbalanced two way analysis of variance, preceded by a prerequisite test analysis, namely a normality test using Lillieforsâ method and a homogeneity test using Bartlettâs method. Based on the results of the hypothetical testing, it could be concluded as follows. (1) The TPS learning model aided by interactive media is better than the TPS and direct learning models, while the TPS learning model is as good as the direct learning model. (2) The academic achievements of students studying mathematics having an auditory learning style were better than students having a visual and kinesthetic style, while the results of students having a visual style was as good as that of those having a kinesthetic style. (3) The differences of students academic achievement depended on the learning model. (4) The effectiveness of learning models depended on students learning style.Keywords: TPS Interactive Media, TPS, Direct Learning, Learning Style, Academic Achievements Studying Mathematics.Â Â